Effects of cervicothoracic mobility programme on pain, range of motion and function in patients with chronic back pain - Naseer, Amna; Shakil Ur Rehman, Syed; Fatima, Ghulam; Ikram, Mehwish (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the effects of the cervicothoracic mobility programme on pain, range of motion and function in patients with chronic back pain. Method: The randomised controlled trial was conducted from April to November 2022 at the Physiotherapy Department of Syed Medical Complex, Sialkot, Pakistan, and comprised patients of either gender aged 18-50 years who had a minimum of 6 months of chronic back pain with moderate disability. They were randomly allocated to experimental group A and control group B. Group A subjects received cervical and thoracic mobilisation with conventional physical therapy, while group B subjects received conventional physical therapy alone. The treatment duration was 45 minutes per session, with 3 sessions per week for 3 weeks. Numeric Pain Rating Scale, Oswestry Disability Index and a goniometer was used to assess pain, disability and for the range of motion. Data was analysed using SPSS 25. Results: Of the 44 patients, 22(50%) were in each of the 2 groups. Group A had 14(63.6%) females and 8(36.4%) males with overall mean age 36.45±10.80 years, while group B had 16(72.7%) females and 6(27.3%) males with overall mean age 35.77±11.05 years. There was a significant inter-group difference in terms of pain, function and flexion (p<0.05), while the difference was not significant in terms of extension, right and left lateral rotation (p>0.05). Intragroup analysis showed significant improvement in both groups (p<0.05). Conclusion: Cervicothoracic mobilisation was more effective in improving pain, functionality and range of motion in patients with chronic low back pain. Key Words: Back pain, Physical therapy modalities, Muscle stretching exercise, Range of motion, Exercise therapy.